Implementing The TSTS-Type Cooperative Model to Improve Student Activity and Critical Thinking in Service Procedures Materials for Class XI SMKN 8 Semarang - Sinta Indraswari; Endiyono; Muntiyani (UM Purwokerto Press, 2024)
This research aims to increase the activeness and critical thinking of class This type of research is classroom action research and was carried out over two research cycles. The research design in each cycle uses four steps/stages of classroom action research, namely, (1) planning, (2) implementation, (3) observation, and (4) reflection. The research subjects were students of class XI Social Work at SMK N 8 Semarang. Data collection was carried out through observation sheets to determine student activity, peer assessments to determine students' critical thinking and observing the implementation of the two stay two stray method, as well as evaluation tests to determine the level of student learning outcomes. The implementation of the two stay two stray method is said to be successful in increasing students' activeness and critical thinking, as evidenced by the results of media presentations produced by students in the process of analyzing existing cases or problems. The results of the research show that the implementation of the two stay two stray method in the learning process can increase the activeness and critical thinking of class.